(3GdcGaj aj UfGYI GdWHs - (3YOfGf GdYjf RQHj , ehab GdOjf CHh fUQ,J (B548 (3g` s
(3ChdgG (B:s
(3deG cGf GdWH jfbSe bSeg Chdjg Edi bSejf (B: (3Yde abW hYde Yed , hcGfJ GdZGjI ajg MaX ehLhOI hQO eabhOI s
(3BNQgG (B:s
(3hEf cGfJ bhJg ajgG eecfI aGLYd dge ai eQb GdaQGQjL Ch eGFgG GdcYc GdeSMhb , Ch dHGH GdNHR aGYde Pdc Ef TGA Gddg JYGdi s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B273s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B189 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B317 s
Keywords: (3GdWHs